Environmental policy and development - Ingo Walter (Intereconomics, 1974)
This study promotes the understanding of the link between development, environment and international economic relations. It suggests that the growth effects of environmental management may tend to serve as an equalizer, helping to redress the imbalance in real income levels between developed and developing economies.
Keywords: 330; Environmental Protection